Frequency of Gynecological Problems in Women on M.D.R. Tuberculosis Treatment - Anila Basit, Wajeeeha Syed, Nadia Ashiq Hussain, Muhammad Nasir, Laraib Aurangzeb (Pakistan Journal of Medical & Health Sciences, 2023)
Multidrug-resistant TB treatment is notorious for being costly, time-consuming, and ineffective. High levels of resistance to isoniazid and rifampicin, with or without resistance to other anti-TB drugs, describe the microbial type of tuberculosis known as multidrug-resistant tuberculosis. Thirdly, MDR-TB has been shown to negatively affect mothers and infants during pregnancy, labor, and the postpartum period. Objective: This Study aimed to determine the frequency of gynecological issues among women receiving therapy for multidrug-resistant T.B. Materials and Methodology: The Obstetrics & Gynecology and department and pulmonology department of Lady Reading Hospital-MTI in Peshawar, K.P., Pakistan, collaborated on a cross-sectional descriptive study. Non-probability sequential sampling was used to get a sample size of 236 using an online G-power tool with a 95% confidence interval. Results: 236 patients were enrolled, with a range of age from 15-24 years (23.3%), 25-34 years (40.4%), 35-44 years (29.2%), and 45-54 years (6.8%). Before treatment, 56.6% were irregular. 42.4% of patients had normal periods. 66.1% had abnormal menstrual cycles after treatment. Before M.D.R. medication, 33.9% of participants had irregular menstrual cycles; throughout MDR-TB treatment, 66.1% of the population had aberrant menstrual cycles. Ploy-menorrhea was 40.7%, and oligo-menorrhea was 59.3%. four contraceptives were surveyed: 3.8% used i.u.c.d., 11.4% pills, 29.7% injectables, and 55.1% barriers. 65.7% had itching and foul-smelling vaginal discharge. 60.2% had dysmenorrhea. infertility was 62%, 55.1% primary, and 44.9% secondary. Conclusion: The Frequency of gynecological disorders that develop in women with MD-TB treatment was determined by this study. Keywords: Multidrug resistance, tuberculosis, Gynaecological problems